Ketergantungan Perilaku Merokok dan Status Gizi Remaja pada Siswa-Siswi Perokok Aktif - Ayudiapala, Deysa; Hermayanti, Yanti; Eriyani, Theresia (Journal of Telenursing (JOTING), 2023)
This study aims to describe the dependence on smoking behavior and nutritional status of active smoker teenagers at SMAN 9 Garut. The method used is a quantitative descriptive method. The research results showed that 36.7% of active smokers at SMAN 9 Garut were not addicted, 28.5% had a low dependency, 33.5% had a moderate dependency, and 1.3% had a high dependency. Meanwhile, the nutritional status was as thin as 52.5%, normal as much as 38.6%, and obesity as much as 8.9%. In conclusion, dependence on smoking behavior is at a moderate level, and nutritional status is poor. However, the level of support for smoking behavior is not a benchmark for decreasing students' nutritional status. This happens because other factors influence the nutritional quality of adolescents. Keywords: Dependent Smoking Behavior, Adolescents, Nutritional Status